К вопросу о частных видовых значениях - Галнайтите, Э. (Kalbotyra, 1978)
The present paper gives a critical review of two notions concerning variant meanings of aspects: 1) when they are traditionally related to the semantics of a verb, as well as the meaning of the formal element of a morphological nature, i. e. prefix or suffix (N. Avilova, I. Golanov. etc.) and 2) when they are interpreted in terms of the variant theory (J. Maslov, A. Bondarko, O. Rassudova, M. Sheliakin, etc.). The author considers both theories disputable.The author maintains (and proves it in the present paper) that absolute meanings of aspects are monolitic and devoid of variant meanings. All context-based meanings are aspectual-contextual and they do not modify absolute meanings of imperfective and perfective aspects. It is consequently reasonable to suppose that they should be attributed not to the grammatical semantics of aspe:ts but to the functioning of aspects in speech.